A time‐resolved live cell imaging assay to identify small molecule inhibitors of FGF2 signaling. Issue 16 (7th June 2019) - Ahmed, Mennatallah; Legrand, Cyril; Yagüe Relimpio, Ana; Beretta, Carlo A.; Muschko, Alina; Wegehingel, Sabine; Müller, Hans‐Michael; Sehr, Peter; Will, David W.; Lewis, Joe D.; Nickel, Walter
Abstract : Fibroblast growth factor 2 (FGF2) is a cell survival factor with crucial functions in tumor‐induced angiogenesis. Here, we describe a novel time‐resolved FGF2 signaling assay based upon live cell imaging of neuroblastoma cells. To validate this system, we tested 8960 small molecules for inhibition of FGF2 signaling with kinetic resolution. Hit compounds were validated in dose‐response experiments for FGF2 signaling, FGF receptor antagonism, downstream ERK phosphorylation and FGF2‐dependent chemoresistance in a cellular leukemia model system. The new screening system for FGF2 signaling inhibitors has unique features, deselecting compounds with pleiotropic effects on cell proliferation and, along with the experimental pipeline reported, great potential for the discovery of new classes of FGF2 signaling inhibitors that block FGF2 dependent tumor cell survival. Abstract :